Cu(i)-Catalyzed amino-yne click polymerization. Issue 48 (23rd September 2016) - He, Benzhao; Zhen, Shijie; Wu, Yongwei; Hu, Rongrong; Zhao, Zujin; Qin, Anjun; Tang, Ben Zhong
Abstract : The first example of Cu(i )-catalyzed regio-specific and stereo-selective amino-yne click polymerization was established. Abstract : The hydroamination reaction of alkynes has been widely studied, but has not been developed as a powerful tool for polymer synthesis. Herein, a novel Cu(i )-catalyzed polyhydroamination has been developed for the facile preparation of nitrogen-containing polymers. This polymerization proceeded smoothly in bulk with 100% atom utilization in a regio-specific and stereo-selective fashion, producing polyenamines with well-defined structures and high molecular weights (up to 13 470) in high yields (up to 97%). Thus, this polymerization is a kind of amino-yne click polymerization. The resulting polymers possess excellent solubility, high thermal stability, strong UV-light shielding efficiency, and good visible light transparency. Considering the high efficiency, ready monomer availability and excellent performance of the products, this Cu(i )-catalyzed amino-yne click polymerization opens up enormous opportunities for preparing functional polymers.